2013
DOI: 10.1152/ajpgi.00246.2012
|View full text |Cite
|
Sign up to set email alerts
|

Oral glutamine supplementation improves intestinal permeability dysfunction in a murine acute graft-vs.-host disease model

Abstract: Although a profound barrier dysfunction has been reported, little is known about the pathophysiological mechanism evoking gastrointestinal graft-vs.-host disease (GI-GvHD) and apparent therapeutic options. The aim of this study was to evaluate the influence of oral glutamine on the course of GI-GvHD in an acute semiallogenic graft-vs.-host disease (GvHD) in irradiated B6D2F1 mice. An acute semiallogenic GvHD was induced by intraperitoneal injection of lymphocytes from C57BL/6 mice to irradiated B6D2F1 mice. Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
1
16
2
Order By: Relevance
“…These data suggest that the protective effects found in the present study did not primarily result from an effect of the amino acid on intestinal barrier function. Differences between our results and those of others might have resulted from differences in animal models (e.g., models of inflammatory bowel disease, gastrointestinal infections, and mucositis vs. models of WSD-induced NAFLD) as well as the amount of Gln supplemented (here, 2.1 g/kg vs. 4.4% wt:wt or 450 mg/kg) and differences between species (e.g., mice vs. rats) (13,(33)(34)(35).…”
Section: Discussioncontrasting
confidence: 71%
“…These data suggest that the protective effects found in the present study did not primarily result from an effect of the amino acid on intestinal barrier function. Differences between our results and those of others might have resulted from differences in animal models (e.g., models of inflammatory bowel disease, gastrointestinal infections, and mucositis vs. models of WSD-induced NAFLD) as well as the amount of Gln supplemented (here, 2.1 g/kg vs. 4.4% wt:wt or 450 mg/kg) and differences between species (e.g., mice vs. rats) (13,(33)(34)(35).…”
Section: Discussioncontrasting
confidence: 71%
“…Some studies showed that glutamine deprivation decreases transepithelial resistance of tight junction proteins, including claudin-1 and occludin (40). Although Noth and coworkers (11) reported that glutamine improved intestinal permeability dysfunction by increasing occludin expression, we did not observe occludin mRNA upregulation in the groups that were subjected to the exhaustive test (11). In conclusion, chronic AG administration protected intestinal barrier function against the impact of acute exhaustive exercise by reducing intestinal permeability and modulated the mRNA expression of claudin-2.…”
Section: Discussioncontrasting
confidence: 62%
“…Glutamine is a major substrate for enterocytes and cells of the mucosal immune system and accelerates the repair of damaged intestinal mucosa and barrier function (10,11). Glutamine, however, presents limited solubility and has a tendency to hydrolyze into potentially toxic glutamate.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for this discrepancy might be due to metabolic, genetic, or epigenetic differences between cancer cells and normal intestinal epithelial cells (Meadows et al 2008). In a recent study, Noth and his colleague demonstrated that oral Gln supplementation ameliorated intestinal permeability dysfunction as shown by increased occludin expression, reduced gastrointestinal permeability and reduced apoptotic cells in the crypt (Noth et al 2013). All these in vivo and in vitro data suggest an important role for tight junction in the maintenance of gut function.…”
Section: Gln and Tight Junctionmentioning
confidence: 95%